The cosemanticness of Kaiser hulls of fixed classes of models - Yeshkeyev, A.R.; Tungushbayeva, I.O.; Koshekova, A.K. (Bulletin of the Karaganda University. Mathematics Series, 2024)
In this article, within the framework of the study of Jonsson theories, the model-theoretic properties of cosemanticness classes belonging to the factor set of the Jonsson spectrum of an existentially closed models’ subclass of some Jonsson theory in a fixed language were studied. Various results have been obtained. In particular, the properties of the cosemanticness of models and classes of models are considered; some results concerning the Jonsson equivalence in generalization for classes of existentially closed models are obtained; a criterion for the cosemanticness of J-classes in connection with their Kaiser hulls has been found.